A Clonal Expression Biomarker Associates With Lung Cancer Mortality - Biswas, Dhruva (Nat Med, 2019)
Molecular biomarkers aim to stratify cancer patients into disease subtypes predictive of outcome, improving diagnostic precision beyond clinical descriptors such as tumour stage(1). Transcriptomic intra-tumour heterogeneity (RNA-ITH) has been shown to confound existing expression-based biomarkers across multiple cancer types(2–6). Here, we analyse multi-region whole-exome and RNA sequencing data for 156 tumour regions from 48 TRACERx patients to explore and control for RNA-ITH in non-small cell lung cancer (NSCLC). We find that chromosomal instability (CIN) is a major driver of RNA-ITH, and existing prognostic gene expression signatures are vulnerable to tumour sampling bias. To address this, we identify genes expressed homogeneously within individual tumours that encode expression modules of cancer cell proliferation and are often driven by DNA copy-number gains selected early in tumour evolution. Clonal transcriptomic biomarkers overcome tumour sampling bias, associate with survival independently of clinicopathological risk factors, and may provide a general strategy to refine biomarker design across cancer types.